The accumulation characteristics and potential health risks of heavy metals in vegetables from reclaimed area of China. Issue 4 (19th May 2018) - Chen, Yongchun; Yuan, Liang; Xu, Chong
ABSTRACT: The reclamation of subsidence area was regarded as a useful pathway to rebuild landscape and ecosystem. However, the elevated concentrations of heavy metals in the reclaimed area may lead to potential environmental and health risks. This study was aimed at investigating the accumulation of heavy metals in the soils and vegetables, and evaluate the potential health risks to human beings via consuming these vegetables. The concentrations of heavy metals (Cd, Cu, Pb, and Zn) were measured by using inductively coupled plasma mass spectrometry. The elevated concentrations of heavy metals were found in the soil from the reclaimed area when compared with the background value. The concentrations of heavy metals were various among the different vegetable species. The heavy metal tolerance could be found in all the selected vegetables. The elevated concentrations of Cu, Pb, and Zn in the edible part of the selected vegetables indicated that the consumption of these vegetables may lead to potential health risk. The intake of soybean, radish, sweet potato, and mugwort may lead to potential health risks due to the elevated target health quotients. Chinese cabbage and pepper were regarded as the suitable vegetables which may help in reducing the potential health risk.